STUDENTLERDIŃ ORATORLÍQ KOMPETENCIYASÍN RAWAJLANDÍRÍW - Abatova, M. (SCIENCE and SOCIETY, 2025)
This article talks about the importance of developing oratory competence in young students and methods of learning speech culture.